Peran Feedback Digital dalam Meningkatkan Kualitas Pembelajaran - Hukom, Julham (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
The development of educational technology has introduced increasingly diverse and interactive forms of digital feedback, significantly impacting the quality of student learning. This article aims to analyze the role of digital feedback from three main perspectives: behaviorist, cognitive, and constructivist. Using a literature review approach, this article integrates recent research findings to explain the concept, characteristics, and pedagogical power of digital feedback in managing learning behavior, facilitating cognitive processes, and supporting knowledge construction. The results and discussion indicate that digital feedback functions to strengthen learning responses and habits from the behaviorist perspective, enhance information processing and reduce cognitive load from the cognitive perspective, and facilitate reflection, collaboration, and meaningful learning from the constructivist perspective. This analysis confirms that the effectiveness of digital feedback is highly dependent on design accuracy, information clarity, and appropriateness to student characteristics. This article provides important implications for educators and learning media developers in designing digital feedback systems that are more adaptive, informative, and centered on student learning needs.